(untitled) (Chemical Bulletin of Kazakh National University, 2025)
The deformation properties, elastic modulus and strength of gelatin films with chitosan, citric acid and L-glutamic acid were studied. According to the results of the study, it was found that the addition of chitosan, citric and L-glutamic acid increases the strength and elasticity modulus of gelatin films. Assessment of the pH effect on the gelatin - chitosan, gelatin - citric acid and gelatin - L-glutamic acid systems provide a representation of their changes in these media. It is assumed that gelatin with L-glutamic acid forms a strong structure at low pH and withstands the conditions of the acidic environment of the stomach, while in an alkaline environment the structural and mechanical characteristics of this system decrease, creating favorable conditions for the release of encapsulated insulin in the intestinal phase. The changes of the physicochemical, structural and mechanical properties of the films under simulated gastrointestinal conditions (pH = 1.0; 4.01; 6.86; 9.18) were determined by IR spectroscopy. The observability of the bands of С-Н, С-ОН, С=O, C-N, N-H, СН(NH2), CH2OH groups in the infrared spectra of films in various pH media is associated with an increase of intermolecular hydrogen bonds and the formation of associative structures.